2005
DOI: 10.2147/tcrm.1.1.39.53597
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems in hospitalized patients on polypharmacy: the influence of age and gender

Abstract: Background: Drug-related problems (DRPs) have been shown to prevail in hospitalized patients, and polypharmacy and increasing age have been identified as two important risk factors. Objective: We investigated the occurrence of DRPs and adverse drug reactions (ADRs) amongst hospitalized patients prescribed polypharmacy, and the association of advanced age and female gender. Method: A retrospective cross-sectional study was performed in an acute-care hospital in Singapore. Only patients prescribed polypharmacy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
98
7
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 50 publications
16
98
7
9
Order By: Relevance
“…The duration of treatment was positively correlated with undesirable drug reactions [24]. The patient's age before and after the recommendations were not correlated and had no effect on the occurrence of DRPs, almost in line with the research conducted by Koh et al [27], which proposed that age does not significantly affect DRPs but the number of the drugs was an important predictor. Increasing age in geriatric patients in this study probably caused physicians to give extra attention to prescribed medication.…”
Section: Resultssupporting
confidence: 56%
“…The duration of treatment was positively correlated with undesirable drug reactions [24]. The patient's age before and after the recommendations were not correlated and had no effect on the occurrence of DRPs, almost in line with the research conducted by Koh et al [27], which proposed that age does not significantly affect DRPs but the number of the drugs was an important predictor. Increasing age in geriatric patients in this study probably caused physicians to give extra attention to prescribed medication.…”
Section: Resultssupporting
confidence: 56%
“…Similar results were reported by Goyal et al (59.3%), Chen et al (68.5%) and Palanisamy et al (59%) in male and (41%) were female whereas Lobo et al and Koh et al concluded in their studies that gender was not a risk factor to develop ADRs. [13][14][15][16][17] In our study age group 41-60 years showed high incidence of ADRs (38.4%) in both the genders. Similar findings were shown by Palanisamy et al who observed the same age group (41-60 years) with 42.71% of ADRs.…”
Section: -12mentioning
confidence: 85%
“…Although polypharmacy has no generally accepted definition, most often it is defined by cut-offs, in terms of the number of medications taken, ranging from two to ten (9)(10)(11)(12). However, regardless of the definition, its prevalence has been reported to rise with age, and is associated with an increased risk of inappropriate drug prescription, under-use of effective treatment, medication errors, poor adherence to pharmacological therapies, drug/drug and drug/disease interactions, and adverse effects (3,(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Many risk factors for polypharmacy have been identified, including demographic aspects such as age, white race, education, sex, poor health, number of chronic diseases, living arrangements, and the number and characteristics health providers (1)(2)(14)(15)(16). Elderly patients with multiple chronic conditions are common in general medicine specialties such as internal and geriatric medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation